2022
DOI: 10.20517/cdr.2021.108
|View full text |Cite
|
Sign up to set email alerts
|

ONECUT2 as a key mediator of androgen receptor-independent cell growth and neuroendocrine differentiation in castration-resistant prostate cancer

Abstract: Despite androgen dependence in a majority of castration-resistant prostate cancers, some cancer cells are independent of androgen receptor (AR) function, a feature of heterogeneity in prostate cancer. One of the aggressive variants of prostate cancer that are AR independent is neuroendocrine prostate cancer (NEPC). This manuscript will focus on the new finding of human one cut domain family member 2 (ONECUT2) transcription factor and its role in castration resistance, especially in NEPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Moreover, GW4869 treatment significantly inhibited the survival of PTX-resistant prostate cancer cells in a dose-dependent manner and reduced the tumor weight in an in vivo model. Kushwaha et al (2022) performed a critical review and demonstrated the role of prostate cancer stem-like cells (PCSCs) in the development of antiandrogen resistance [8] . PCSCs have the ability to differentiate, selfrenew, and regenerate tumor heterogeneity.…”
Section: Article Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, GW4869 treatment significantly inhibited the survival of PTX-resistant prostate cancer cells in a dose-dependent manner and reduced the tumor weight in an in vivo model. Kushwaha et al (2022) performed a critical review and demonstrated the role of prostate cancer stem-like cells (PCSCs) in the development of antiandrogen resistance [8] . PCSCs have the ability to differentiate, selfrenew, and regenerate tumor heterogeneity.…”
Section: Article Descriptionmentioning
confidence: 99%
“…The methods for isolation, identification, and characterization of PCSCs from primary prostate tumors have also been described. Choi et al (2022) provided a perspective on the transcription factor ONECUT2 which mediates ARindependent cell growth and neuroendocrine differentiation in CRPC [9] . It is a key factor in NE differentiation between adenocarcinoma to neuroendocrine prostate cancer (NEPC).…”
Section: Article Descriptionmentioning
confidence: 99%
“…ONECUT transcription factor family is involved in tumorigenesis. While ONECUT1 is associated with liver development and differentiation, ONECUT2 regulates cell proliferation, migration, adhesion and differentiation ( Choi et al, 2022 ). Elevated expression levels of ONECUT2 have been reported in various cancers, particularly in NEPC ( Choi et al, 2022 ).…”
Section: Other Transcription Factorsmentioning
confidence: 99%
“…While ONECUT1 is associated with liver development and differentiation, ONECUT2 regulates cell proliferation, migration, adhesion and differentiation ( Choi et al, 2022 ). Elevated expression levels of ONECUT2 have been reported in various cancers, particularly in NEPC ( Choi et al, 2022 ). Therefore, ONECUT2 overexpression marks the onset of cancer progression and metastasis.…”
Section: Other Transcription Factorsmentioning
confidence: 99%